Use of radiofrequency in the treatment of grade III fibrous edema of the gluteal gland: A literature review (Research, Society and Development, 2023)
The skin, being the largest organ in the human body, plays a crucial role in both protection and aesthetics. Geloid fibro edema (FEG), commonly known as cellulite, is an aesthetic dysfunction categorized into four degrees that can affect the integrity of the skin. Radiofrequency is a therapeutic modality of dermatofunctional physiotherapy that uses a high-frequency current device to generate heat by conversion in human body tissues. This study aims to evaluate the effectiveness of radiofrequency in improving grade III fibro geloid edema in the gluteal region. It is configured as a systematic literature review whose objective was a comprehensive search of scientific articles carried out through electronic sources, including Google Scholar, SCIELO (Online Electronic Scientific Library), VHL (Virtual Health Library) and PUBMED. The research period covers the years 2010 to 2023. It is expected that, in the end, significant improvements will be observed in grade III fibro geloid edema in patients undergoing the radiofrequency technique. The application of this treatment aims to achieve superior results in reducing cellulite and improving the appearance of the skin, thus contributing to promoting the health and well-being of participants.